ILUSI FISKAL DAN PENGARUHNYA TERHADAP PERTUMBUHAN EKONOMI DAN KESEJAHTERAAN MASYARAKAT - Ayu Dyan Febrianti; Rudy Badrudin (LPPM STIE YKPN Yogyakarta, 2023)
This study aims to identify the occurrence of the phenomenon of fiscal illusion in the influence of Regional Taxes, General Allocation Funds, Special Allocation Funds on Regional Expenditure and their influence on Economic Growth and Social Welfare in East Java Province in 2015-2018. The type of data used is secondary data. The object of research includes 38 regencies/cities in East Java Province with data sources obtained from Reports on Budget Realization and Economic Growth and Social Welfare. The analytical method used is Partial Least Square analysis. The conclusion obtained from the test is that Regional Taxes have a positive and significant effect on Regional Expenditures, General Allocation Funds have a positive and significant effect on Regional Expenditures, Special Allocation Funds have a positive but not significant effect on Regional Expenditures, Regional Expenditures have a positive and significant effect on Economic Growth, Growth The economy has a positive but not significant effect on people's welfare. There is a phenomenon of fiscal illusion where fiscal illusions have a positive and significant effect on economic growth but not a significant positive effect on social welfare in the regency/city of East Java Province in 2015-2018.